Klasterisasi Minat Baca Mahasiswa Menggunakan Metode K-Means - Rosman, Edwar; Ikhsan, Fathurrahman Kurniawan (JURTEII: Jurnal Teknologi Informasi, 2024)
One of the ways to increase student interest in reading can be done by increasing the collection of books in the Kerinci IAIN library. But so far to determine the collection of books to be added is still done manually, so it takes a long time, besides that the process of adding books which refers to the statistics of borrowing the most books makes the collection of books less diverse. For this reason, a book collection clustering method is needed using the k-Means method to obtain optimal results. Book collections are grouped into 3 clusters, that is, considerations need to be added, priorities to be added and not need to be added can be a reference for librarians in maximizing the process of adding book collections. To facilitate the collection of book collections, RapidMiner software is used to get fast and accurate results